2001
DOI: 10.1108/02634500110408286
|View full text |Cite
|
Sign up to set email alerts
|

Consumers and brands: a study of the impact of self‐image congruence on brand preference and satisfaction

Abstract: Previous research indicates that the self‐image product image congruity (commonly known as self‐image congruence) can affect consumers’ product preferences and their purchase intentions. Self‐image congruence can also facilitate positive behaviour and attitudes toward products. This paper reports findings from a research study which was conducted to determine the effect of self‐image congruity on brand preference and satisfaction in the precious jewellery market in the UK. A questionnaire was sent to 500 consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
195
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(217 citation statements)
references
References 53 publications
12
195
1
9
Order By: Relevance
“…On the contrary, it was identified that brand image could not influence customer satisfaction with low-priced cosmetic brands. This implies that self-image congruity is a good predictor variable of consumers' brand preferences and consumer satisfaction [12]. Besides confirming the findings of previous studies, this study uniquely contributed to brand image literature.…”
Section: Discussionsupporting
confidence: 73%
“…On the contrary, it was identified that brand image could not influence customer satisfaction with low-priced cosmetic brands. This implies that self-image congruity is a good predictor variable of consumers' brand preferences and consumer satisfaction [12]. Besides confirming the findings of previous studies, this study uniquely contributed to brand image literature.…”
Section: Discussionsupporting
confidence: 73%
“…Self-image congruity was a very strong predictor of consumer's brand preferences and a good predictor of consumer satisfaction. And consumers with higher levels of self-image congruity were more likely to prefer the brand and enjoy higher levels of satisfaction with the brand as compared to those with lower levels of self-image congruity (Jamal & Goode, 2001). Several previous researches provide evidence about the positive effect of self-image congruity in the tangible product context (only for the actual and the ideal self-image congruity) on overall attitude (Ericksen & Sirgy, 1992;Kleijnen, 2005), and purchase intentions (Ericksen, 1996;Mehta, 1999).…”
Section: Personal Fitmentioning
confidence: 94%
“…Kendi benlik imajına benzer bir markayı tercih etme eğilimi "İmaj Uyumu Hipotezi" olarak adlandırılmaktadır. Birçok çalışmada benlik imajı ile marka tercihi arasında pozitif yönlü bir ilişki olduğu tespit edilmiştir (Belk, Bahn & Mayer, 1982;Onkvist & Shaw, 1987;Hong & Zinkhan, 1995;Graeff, 1997;Heath & Scott,1998;Jamal & Goode, 2001;King, 2002;Gross & Brown, 2006;He & Mukherjee, 2007). Carroll ve Ahuvia, (2006, s. 82) tüketiciyi ifade eden markayı, belirli markanın kişinin sosyal benliğini arttırma ve / veya kişinin kendi özünü yansıtma derecesi ile ilgili tüketicilerin algıları olarak tanımlamıştır.…”
Section: Marka Aşkı Ve Benliği İfade Eden Markalar Arasındaki İlişkiunclassified